2021
DOI: 10.3389/fphar.2021.670170
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Corticosteroid Administration in Coronavirus Disease 2019 Outcomes: An Umbrella Meta-Analysis Incorporating Both Mild and Pulmonary Fibrosis–Manifested Severe Disease

Abstract: Background: Effective treatments for coronavirus disease 2019 (COVID-19) are urgently needed. The real role of corticosteroid use in COVID-19 has long been of interest and is disputable.Methods: We aimed to quantitatively reevaluate the efficacy of corticosteroids on COVID-19. Databases were searched for eligible meta-analyses/systematic reviews with available outcome data. For each association, we estimated the summary effect size with fixed- and random-effects models, 95% confidence intervals, and 95% predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
(98 reference statements)
0
7
0
Order By: Relevance
“…Inpatient corticosteroid duration of >15 days has been associated with a higher risk of CAPA [ 8 ]. Systematic reviews and meta-analyses have found that long-term corticosteroid use prior to hospital admission is a relevant risk factor for CAPA [ 18 , 19 ]. However, many studies included did not specify doses or total duration of corticosteroids received [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inpatient corticosteroid duration of >15 days has been associated with a higher risk of CAPA [ 8 ]. Systematic reviews and meta-analyses have found that long-term corticosteroid use prior to hospital admission is a relevant risk factor for CAPA [ 18 , 19 ]. However, many studies included did not specify doses or total duration of corticosteroids received [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews and meta-analyses have found that long-term corticosteroid use prior to hospital admission is a relevant risk factor for CAPA [ 18 , 19 ]. However, many studies included did not specify doses or total duration of corticosteroids received [ 18 , 19 ]. We aimed to evaluate the risk of CAPA with typical COVID-19 corticosteroid treatment durations (≤10 days) and prolonged durations (>10 days).…”
Section: Discussionmentioning
confidence: 99%
“…Since none of the healthy nor recovered BALF showed fibrin clot formation, it suggests that the presence of activated thrombin in C3263 BALF is related to the SARS-CoV-2 infection in the patient. The clinical risk of developing pulmonary pathology associated with COVID has not been well characterized, although preexisting pulmonary conditions, severity of infection and the presence of inflammatory factors appear to predict the risk of COVID-associated lung damage [61][62][63][64][65][66] . Our findings suggest the concentrations of prothrombin, fibrinogen and other coagulation factors in SARS-CoV-2 infected lung fluids may be used to indicate the risk of COVID-associated lung pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Cheng B, et al . [ 20 ] also concluded that SD of corticosteroid administration was associated with a 27% risk reduction in mechanical ventilation (hazard ratio [HR]: 0.73 [0.64–0.83]) and a 20% reduction in the mortality of critically ill/severe COVID-19 patients (HR: 0.80 [0.65–0.98]).…”
Section: Discussionmentioning
confidence: 99%